Uncovering Gender Disparity in Margaret Atwood’s The Blind Assassin - Aditya Ridho Fatmawan; Jesica Vanessa Hutapea; Ni Made Ignityas Prima Astuti (Universitas Musamus Merauke, 2024)
Mostly telling about Iris Chase, The Blind Assassin projected a series of complex circumstances that happened in her family and marriage lives. Realizing that this novel also contains gender issues, therefore this study focused on gender differences by the characters portrayed in The Blind Assassin, a historical fiction novel by Margaret Atwood. Due to a number of considerations, the content of the novel tickled this curiosity about how gender differences occur in the novel, to which this will lead to the prime discussion of this analysis. The data were collected by adapting Miles and Huberman’s qualitative research model. Through analyzing the content and meaning of the text, this research applied McKee’s textual analysis (2003) in order to describe and reveal the messages contained in the novel. Based on the results of existing data analysis, it was found that gender differences occur in some parts of the novel. Furthermore, the major difference was noticed on the gender inequality between men and women. It was strengthened by the data that the men characters were significantly dominant rather than the women characters in the novel.